Propulsive strength training in wheelchair tennis to improve service response - Salierno, M.; Esposito, G.; Izzo, R.; Fattore, S.; D'Isanto, T. (Journal of Human Sport & Exercise, 2021)
In wheelchair tennis, the biomechanical-bioenergetic quantitative aspects involved are the fast force and maximum isometric propulsion force of the race medium. The problem encountered is to improve the propulsion force of the race medium, therefore the thrust force, to increase the strength of the upper limbs in the response to the service. The aim of the study is to verify the effects of a training with upper limb overloads on sports performance, in particular the response to the service. A sample of 30 paraplegic athletes, of an average age of 25 years, with a D8-D12 back injury, of the Open category, has been recruited. Athletes have been training with upper body overloads for 2 months with a frequency of 2 times a week. The 20m sprint test was executed after and before the two months. The T-test for dependent samples was used to detect the difference between the two groups (p < .05). Training with upper limb overloads showed a significant improvement (p < .05) of 42% in service response. According to the results, athletes from an average initial performance level of 5.2 have moved to an average level of 4.82, which corresponds to an almost excellent level. Overload training has proven effective in increasing fast strength in response to the technical gesture of the opponent's service.